A MODALITAS KANDIDAT PETAHANA DPRD KOTA PALU PADA PEMILU 2024 - Irwansyah Kamindang; Meldi Amijaya; Nurhayati Hamid (LPPM Universitas Abdurrab, 2025)
Incumbent candidates often possess advantages over newcomers in elections, particularly in name recognition, campaign resources, and experience. However, these advantages do not always guarantee victory, especially when voters are dissatisfied with the incumbent’s performance. This study aims to analyze the modalities of incumbent candidates and elected members of the Palu City Regional House of Representatives (DPRD) in the 2024 election using a qualitative method with a case study approach, based on four dimensions of capital, economic, social, cultural, and symbolic. Data were collected through in depth interviews, observations, and documentation. The findings reveal that political success is not solely supported by economic, cultural, symbolic capital, or structural positions. Success is more strongly determined by the effective management of social capital, as well as the ability to build trust and closeness with the community. The failure of incumbents in this study reflects a lack of adaptation to social dynamics and suboptimal management of social relations in response to changing conditions, while the success of new candidates highlights the importance of a strong social base and responsive communication strategies. These findings underscore the need for political actors to focus on communication strategies and strengthening constituent relationships rather than merely relying on material resources or structural positions.